Parent Work in the Development and Teaching of Child Analysis. Issue 1 (31st December 2022) - Barrett, Denia
ABSTRACT: This paper traces a line from the early psychoanalytic pioneers working as parents, to those whose approach seemed to be to work on parents, to those who explored working via the parents, and concludes with the contemporary practice of working with parents as partners in child analysis. The inclusion of parenthood and parent work in didactic training, supervision, and analysis during and after training is elaborated.